Pregnancy in a woman with recurrent immunoglobulin a nephropathy: A case report - A. Carosso; M. Zonca; L. Colla; F. Borella; L. Daniele; C. Benedetto (Elsevier, 2018)
Immunoglobulin A nephropathy (IgAN) is the most common form of primary glomerulonephritis and is increasingly encountered in pregnancy. The obstetric and renal outcomes of pregnancy are controversial, however. Women with IgAN are at higher risk of hypertension, preeclampsia and foetal loss; the prognosis is worse for those who have advanced chronic kidney disease and proteinuria. Here we report the case of a 32-year-old nulliparous woman with chronic hypertension who conceived during an active phase of her IgAN, which had been diagnosed 8 years earlier. Antihypertensive therapies and a low-protein diet were key to her reaching 34 weeks' gestation with acceptable kidney function. Rupture of membranes occurred at 34 weeks 3 days' gestation and a healthy boy was delivered the next day. This report aims to provide clinicians with useful information for the management of patients with IgAN during pregnancy. Keywords: Immunoglobulin a nephropathy, Pregnancy, Chronic kidney disease, Renal function, Proteinuria